PCR : clinical diagnostics and research - Rolfs, Arndt (Springer, 1992)
The \"how-to\" book for every laboratory using PCR! Complete information aboutPCR procedures, combined with the discussion of contemporary opinions, givesa good overview of this multifaceted method and its applications. Even experienced laboratories will welcome the clear presentation of demanding procedures such as the exact quantification of PCR products or the in-situ PCR. Protocols that have been tried and tested provide swift support for troubleshooting all sorts of procedural problems. Indeed, many examples of problem areas found in diagnostically oriented PCR are fully described. Furthermore, the most important lab PCR equipment as well as the pros and cons of single individual reaction components which are necessary for performing PCR reactions are discussed. The book is clearly organized to give an introduction to each technique, brief background information, step-by-step instructions for carrying out the procedure and additional comments.
Keywords: Clinical Laboratory Techniques; klinické laboratorní techniky; Polymerase Chain Reaction; polymerázová řetězová reakce; biologie; Molecular Biology; molekulární biologie